SINTESIS PIRAZOLIN DARI KALKON 3-KLORO INTI NAFTALEN DAN UJI AKTIVITASNYA SEBAGAI ANTIBAKTERI - Ary Puspita; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pyrazolines have been reported to possess many of interesting biological activities such as antimicrobial,  antidepressant,  antitumor, antioxidant, antiinflammatory, anticancer and  anticonvulsant  activity .  In this research, a  compound  of 1-phenyl-3-(2-naphthyl)-5-(3-chlorophenyl)-2-pyrazoline  was synthesized by cyclization of  (E)-3-(3-chlorophenyl)-1-naphthalene-2-yl-prop-2-en-1-on and phenylhydrazine  using glacial acetic acid  as  a  catalyst under  microwave  irradiation. The compound showed a good yield and  it  was characterized by UV, IR, 1 H-NMR  and 13 C-NMR  spectroscopy. The antibacterial activity of this compound was determined using agar diffusion method against Gram positive bacteria  (Bacillus subtilis  and  Staphylococcus aureus) and Gram negative bacteria  (Escherichia coli  and  Salmonella typhi). The compound showed very poor activity against Salmonella typhi.